IMPLEMENTASI ALGORITMA AES DAN BCRYPT UNTUK PENGAMANAN FILE DOKUMEN - Gebrina Divva Meuthia Zulma, (2022)
With the current development of Covid-19 case, The public is advised to reduce outside activities, so Microsoft Office and PDF are very important for data exchange. Unfortunately, the data becomes vulnerable to attack, so cryptography is needed so that document files can be protected. It is necessary to make a web-based application using the Laravel framework where document files will be encrypted using AES 256 then the secret key will be hashed using Bcrypt. The expected results of the research are a web that can be used to secure document files using AES and Bcrypt.